The Art of Public Speaking: Mastering the Art of Effective Communication (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The art of public speaking is a communication skill required by all. if you are an effective speaker, you will enhance your Prestige, influence decisions and come to occupy more important Positions. in Fact, skill in Oral Presentation is an important equipment for life. The advice Shakespeare gave more than 350 years ago is still valuable and worth remembering:Mend your speech a little, Lest it may mar your fortune.The factors which are peculiar to oral Presentation are the use of body language, Correct Posture, Eye-Contact, Voice modulation and Presentation Plan.